The Brazilian government severance indemnity fund for employees (FGTS) and unemployment insurance savings accounts in other countries: A comparative analysis of their effects on the labour market - Ana Luiza Neves de Holanda Barbosa; Miguel Nathan Foguel; Charlotte Bilo (International Policy Centre for Inclusive Growth (IPC-IG), 2017)
The main objective of passive employment policies is to guarantee a certain level of consumption and well-being for workers who lose their jobs. These policies also aim to assist the unemployed in searching for a new job and to improve the matching between employers and workers to generate positive effects on the duration of employment, productivity and wages. Most passive employment policies consist of cash transfers for unemployed people. From a cyclical point of view, unemployment protection systems can help stabilise the economy in times of crisis, stimulate labour formalisation (especially in developing countries) and, in some cases, increase savings, especially in the long term. [...]
Keywords: 330; Brazil; Government; Severance; Indemnity; Fund; Employees; FGTS; unemployment; insurance; savings; accounts; countries; comparative; analysis; effects; labour; market